STRIDER: Steric hindrance and metal coordination identifier. (June 2022) - Patro, L. Ponoop Prasad; Rathinavelan, Thenmalarchelvi
Abstract: Biomolecular structural knowledge is important to understand the biological processes and the mechanisms underlying human diseases. In silico modeling plays a vital role in de novo design and docking of biomacromolecules as well as in exploring their conformational dynamics. Additionally, it has a major role in acquiring the structural insights using the parameters derived from experimental techniques such as cryo-electron microscopy. Steric hindrance is one of the important measures to validate the accuracy of the modeled biomolecular structures. A web user interface (WUI), namely, STRIDER (st eric hindr ance and metal coordi nation id entifier ) (www.iith.ac.in/strider/ ) estimates and reports pairwise inter- and intra- molecular steric hindrances using the van der Waals radius of 117 elements. STRIDER identifies and reports the coordination pattern of 64 metals in an interactive mode. It can provide conformer wise interaction pattern(s) of an ensemble of conformers which is needed in circumventing sampling issue in flexible docking, protein folding and structure based virtual screening. Further, it generates a pymol session file which highlights the aforementioned interaction for an offline analysis. Since STRIDER simply requires the Cartesian coordinates of a molecule in PDB format, any chemical structure can be given as an input. Functionality of STRIDER is illustrated here by considering several examples. Graphical Abstract: ga1 Highlights: STRIDER estimates pairwise inter- and intra- molecular short-contacts using the van der Waals radius of 117 elements. STRIDER provides an interactive view of all the short-contact regions for a single conformer or an ensemble of conformers. STRIDER identifies and reports the coordination pattern of 64 metals in an interactive mode. STRIDER can act as an essential tool in modeling the three-dimensional structure of any biomolecules.